Padrões de uso e gramaticalização de agora e então - vol.1 - Rodrigues, Fernanda Costa Demier (2009)
The aim of this research is to analyze in an interpretative way , by the functionalist perspective, the patterns of use and the grammaticalization process time > text of agora and então in different periods of time in a panchronic perspective. We believe that this process happens in a unidirectionality way. From the corpus formed by novels and theatre plays of four different synchronies ( Latin synchrony (from Latin period up to 13th century); archaic synchrony (from 13th century up to 15th century); classic synchrony ( from 15th century up to 18th century); and modern synchrony (from 19th century up to 21st century), the analyzed terms and structures are observed as elements that reflect sense and form modifications while they are used because of interactional interference, frequency of use, besides cognitive influences. It is to be noted that these items has both grammatical and discourse uses. Their traditional uses are linked to the time adverb category and constitute, in this class, categorical prototypes formed by the features [+ time reference], [+ mobility] and [+ verbal scope]. During the trajectory, there is a categorical migration, in which agora and então acquire the features [+ fixation] and [+ clause scope]. This last characteristic has the variation [+ connection] and [+ discourse markdness]. These functional uses of the terms have been occurring since Latin texts to the contemporary ones in a panchronic way.